Computing and justice in Peru - Torres López, Edgardo (2020)
Information technology development extends over all knowledge areas and human action. Justice is not an exception. Legal information technology facilitates specific court areas packed with physical files to become modern courts, administering justice using virtual files, where orality, quality and proper time stand out.The Peruvian Judiciary, as well as that of other Latin American countries, is heading towards this goal progressively, by the progress made in electronic service of process and video hearings